Fetal assessment in buprenorphine‐maintained women using fetal magnetoencephalography: a pilot study. (13th June 2018) - Escalona‐Vargas, Diana; Coker, Jessica L.; Ray‐Griffith, Shona; Siegel, Eric R.; Lowery, Curtis L.; Stowe, Zachary N.; Eswaran, Hari
Abstract: Background and Aims: In‐utero exposure to opioids including buprenorphine (BUP) has been shown to affect fetal activity, specifically heart‐rate variability (FHRV) and fetal movement (FM). Our objective was to extract simultaneous recordings of fetal cardiac and brain‐related activity in BUP‐maintained and non‐opioid exposed pregnant women using a novel non‐invasive biomagnetic technique. Design: A pilot study was conducted, recording and analyzing biomagnetic data from fetuses of BUP‐maintained and non‐opioid exposed pregnant women. Signals were acquired with the non‐invasive 151‐channel SARA (SQUID‐Array for Reproductive Assessment) system. Advanced signal‐processing techniques were applied to extract fetal heart and brain activity. Setting: University of Arkansas for Medical Sciences (UAMS, Little Rock, Arkansas, USA). Participants: Eight BUP‐maintained pregnant women from UAMS Women's Mental Health Program between gestational ages (GA) of 29–37 weeks who were treated with 8–24 mg of BUP daily. Sixteen pregnant women with no known opioid exposure in the same GA range were also included. Measurements: Outcome measures from the fetal heart and brain signals included: heart rate (FHR), FM, FHR accelerations, FHR–FM coupling, FHRV, fetal behavioral states (FBS) and power spectral density (PSD) of spontaneous brain activity. These measures were analyzed at three GA intervals. Findings: Fetal heart and brain activity parameters were extracted and quantified successfully from 18 non‐opioid and 16 BUP recordings. Overall analysis in both groups show that: FHR and FM ranged from 131 to 141 beats per minute (b.p.m.) and 5 to 11 counts, respectively. In the 35–37 weeks GA, the coupling duration (~9 s) was the shortest, while three of the FHRV parameters were the highest. The PSD of brain activity revealed highest power in 0.5‐4 Hz bandwidth. Transitions in FBS from quiet to active sleep were > 50% of sessions. Conclusions: This pilot study showed that a novel biomagnetic technique allows simultaneous quantification of cardiac and brain activities of a group of buprenorphine‐exposed and non‐exposed fetuses in the third trimester.